STRATEGI PEMERINTAH DESA NANGGARJATI HUTA PADANG KABUPATEN TAPANULI SELATAN DALAM PENGEMBANGAN OBYEK WISATA BERBASIS MASYARAKAT (COMMUNITY BASED TOURISM) TAHUN 2021-2022 - Abdul Majid Siregar; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Nanggarjati Huta Padang Village is one of the tourist villages in South Tapanuli Regency. The lack of concern for the village government in developing tourism objects that have been stipulated in the South Tapanuli Regent Regulation Number 64 of 2020, can be seen from the inadequate facilities and accommodations and the village tourism development budget that has not been budgeted for in the Village RKP and RPJM. In addition, culinary SMEs typical of North Sumatra, especially South Tapanuli, are still powerless, both due to limited capital, low technology and skills, as well as limited market access and the absence of integrated and directed culinary development initiatives from the government. Evidenced by the small number of South Tapanuli-style processed food outlets. The aim of the research is to find out the strategy of the village government of Nanggarjati Huta Padang in developing community-based tourism objects and to find out the inhibiting factors of the village government in developing these tourism objects. This research uses descriptive research with a qualitative approach. Primary data was obtained from interviews, and secondary data was obtained from documents related to the research topic. The data analysis technique used is qualitative data analysis. The results showed that the strategy carried out by Nanggarjati Huta Padang Village in developing tourism objects was to create attractions in the form of developing natural, historical, cultural and artistic tourism objects. Obstacles in carrying out the tourism development strategy in Nanggarjati Huta Padang Village are in the form of budget funds that have not been regulated according to needs and facilities and accommodation that are still inadequate and are still making improvements to date. Keywords: Strategy, Attractions, Attractiveness, Accessibility, Facilities.